Influence of Listening to Jiao Tune on Sleep Quality and Blood Glucose in the Elderly Patients with Type 2 Diabetes Accompanied by Insomnia - Xuxing LIN; Jingmin JI; Guoying ZHOU (康复学报)
Objective:To explore the influence of listening to jiao tune on sleep quality and blood glucose in the elderly patients with type 2 diabetes accompanied by insomnia of liver-fire type.Methods:One hundred and five patients were randomly divided into the jiao tune group, the western music group, and the control group with 35 cases in each group. The jiao tune group listened to jiao tone music, while the western music group listened to western hypnotic music. Participants were required listening to music for one month, 30 minutes before sleep every night, five times a week. Sleep quality and blood glucose were analyzed before and after intervention.Results:After intervention, the total effective rate of the jiao tune group and the western music group were higher than that of the control group (P<0.05), while the total PSQI scores, sleep quality and sleep efficiency were lower than those of the control group (P<0.05). Time of falling asleep of the jiao tone group was better than that of the western music group and the control group respectively. The fasting blood glucose in the jiao tune group and the western music goup was lower than that of the control group (P<0.05).Conclusion:Listening to jiao tone can improve sleep quality, descend fasting blood glucose and reduce the time of falling asleep in the elderly patients with type 2 diabetes accompanied by insomnia of liver-fire type.